2017
DOI: 10.1371/journal.pone.0183924
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of cervical cancer education and provider recommendation for screening on screening rates: A systematic review and meta-analysis

Abstract: BackgroundAlthough cervical cancer is largely preventable through screening, detection and treatment of precancerous abnormalities, it remains one of the top causes of cancer-related morbidity and mortality globally.ObjectivesThe objective of this systematic review is to understand the evidence of the effect of cervical cancer education compared to control conditions on cervical cancer screening rates in eligible women population at risk of cervical cancer. We also sought to understand the effect of provider r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
124
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 94 publications
11
124
2
8
Order By: Relevance
“…To our knowledge, the present study is the first randomized clinical trial in general practice aiming to increase participation of immigrant women in CCS, and it proved to be effective. Our approach concurs with a recent systematic review and meta-analysis on CCS 24 The intervention showed an effect of 2% in the fully adjusted model. This effect size was significant, but smaller than what we expected to achieve.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, the present study is the first randomized clinical trial in general practice aiming to increase participation of immigrant women in CCS, and it proved to be effective. Our approach concurs with a recent systematic review and meta-analysis on CCS 24 The intervention showed an effect of 2% in the fully adjusted model. This effect size was significant, but smaller than what we expected to achieve.…”
Section: Discussionsupporting
confidence: 86%
“…More than a quarter of participants reported that a nurse or doctor had never discussed with them the need for regular cervical cancer screening (73% for women who had never had a Pap smear). As previously reported in the general population, providers have a crucial role to play in the adherence to cervical cancer screening recommendations 31,32 and our results underline the importance of better communicating the need for cervical cancer screening to women with HIV. The specialty of the HIV provider as reported by participants did not change the odds of adherence to cervical cancer screening.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, HPV self-sampling for cervical cancer screening has been shown to be very acceptable and feasible for hard-to-reach women, including ethnic minorities and Indigenous women, 45,46 particularly when the kits are mailed or delivered home in person. 32,[47][48][49] Being in a relationship and sexually inactive increased the likelihood of cervical cancer screening delays, as previously reported by others. 50,51 Explanations about HPV-related cancers need to specify that the risk remains even if a woman is no longer sexually active, because decades can pass between an initial HPV infection and the development of cervical cancer.…”
Section: Opensupporting
confidence: 81%
“…A third barrier is that in many settings, women are often not aware of their reproductive anatomy and health, which can deter positive health-seeking behavior, particularly as it relates to cervical cancer screening. 18 In 2014, the American Congress of Obstetricians and Gynecologists (ACOG) and Women's Health magazine conducted a survey of 7,500 women and found that 64% of them could not identify a picture of the cervix. The same survey found that 54% of women admitted keeping secrets related to their reproductive anatomy from their gynecologists, perhaps out of embarrassment related to issues pertaining to their reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Further, several studies have found that educating women on their cervix and cervical cancer significantly increased cervical cancer screening rates more than two-fold. 18,19,[23][24][25][26][27][28][29] Simply put, giving women access to accurate information and a comprehensive education on their sexual anatomy can significantly improve their understanding of sexual and reproductive health. One strategy to empower women to care and advocate for their reproductive autonomy is the provision of self-exploration technology that facilitates women's visualization, understanding and appreciation of their own vagina and cervix.…”
Section: Introductionmentioning
confidence: 99%